Thermal energy and charge currents in multi-terminal nanorings - Tobias Kramer; Christoph Kreisbeck; Christian Riha; Olivio Chiatti; Sven S. Buchholz; Andreas D. Wieck; Dirk Reuter; Saskia F. Fischer (AIP Advances, 2016)
We study in experiment and theory thermal energy and charge transfer close to the quantum limit in a ballistic nanodevice, consisting of multiply connected one-dimensional electron waveguides. The fabricated device is based on an AlGaAs/GaAs heterostructure and is covered by a global top-gate to steer the thermal energy and charge transfer in the presence of a temperature gradient, which is established by a heating current. The estimate of the heat transfer by means of thermal noise measurements shows the device acting as a switch for charge and thermal energy transfer. The wave-packet simulations are based on the multi-terminal Landauer-Büttiker approach and confirm the experimental finding of a mode-dependent redistribution of the thermal energy current, if a scatterer breaks the device symmetry.